2010
DOI: 10.1186/1471-2164-11-157
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling of a Sinorhizobium meliloti fadD mutant reveals the role of rhizobactin 1021 biosynthesis and regulation genes in the control of swarming

Abstract: BackgroundSwarming is a multicellular phenomenom characterized by the coordinated and rapid movement of bacteria across semisolid surfaces. In Sinorhizobium meliloti this type of motility has been described in a fadD mutant. To gain insights into the mechanisms underlying the process of swarming in rhizobia, we compared the transcriptome of a S. meliloti fadD mutant grown under swarming inducing conditions (semisolid medium) to those of cells grown under non-swarming conditions (broth and solid medium).Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
68
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(77 citation statements)
references
References 62 publications
(91 reference statements)
5
68
0
4
Order By: Relevance
“…On semisolid MM, surface translocation of these two strains was severely affected compared to that of their parental strains although not completely abolished, as is the case for 2011rhbA62 and 1021rhbA, mutant strains unable to produce the siderophore rhizobactin 1021 that are derived from Rm2011 and Rm1021, respectively (Fig. 1C) (32). This result demonstrates that ExpR-deficient S. meliloti strains are able to show flagellum-driven surface translocation (i.e., swarming motility) on semisolid MM, and therefore, we can conclude that ExpR is not required for swarming.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On semisolid MM, surface translocation of these two strains was severely affected compared to that of their parental strains although not completely abolished, as is the case for 2011rhbA62 and 1021rhbA, mutant strains unable to produce the siderophore rhizobactin 1021 that are derived from Rm2011 and Rm1021, respectively (Fig. 1C) (32). This result demonstrates that ExpR-deficient S. meliloti strains are able to show flagellum-driven surface translocation (i.e., swarming motility) on semisolid MM, and therefore, we can conclude that ExpR is not required for swarming.…”
Section: Resultsmentioning
confidence: 99%
“…However, our recent data are in disagreement with these findings. We have reported that the commonly used S. meliloti laboratory strain Rm1021 and the closely related strain Rm2011, both known to have a disrupted copy of expR, are able to swarm on semisolid minimal medium (32). To solve the discrepancies between these reports, in this work, we have reexamined the role played by the expR gene in swarming of S. meliloti.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In R. etli, swarming is regulated by the CinIRS quorum-sensing system, and the long-chain N-acyl homoserine lactone molecules produced by CinI have biosurfactant-like activity and are present in the extracellular matrix secreted by swarmer cells (Daniels et al 2006). Swarming motility has also been demonstrated in Bradyrhizobium japonicum (Covelli et al 2013) and in Sinorhizobium meliloti (Soto et al 2002;Nogales et al 2010;Gao et al 2012). Similar to R. leguminosarum, swarmer cells formed by S. meliloti QS77 are hyperflagellated.…”
Section: Introductionmentioning
confidence: 91%
“…Swarming behaviour is prevalent within the rhizobia (Soto et al 2002;Daniels et al 2006;Braeken et al 2008;Nogales et al 2010;Tambalo et al 2010c;Covelli et al 2013), but little is known regarding the signals and signalling pathways that induce swarmer cell differentiation. Therefore, we initiated this study to investigate the possible effects of host plant seed exudates on the swarming behaviour of R. leguminosarum.…”
Section: Discussionmentioning
confidence: 99%